Florida Dairy Industry Statistics: Herd Performance Measures and Benchmarks - Kathy G. Arriola; Albert De Vries (EDIS)
This 8-page fact sheet summarizes technical performance data of dairy herds in Florida and the Southeast United States collected through the Dairy Herd Improvement (DHI) program. Written by K.G. Arriola and A. De Vries, and published by the UF Department of Animal Sciences, February 2013.